Properties of hemagglutinins newly separated from toxic phytoplankton - Sagir Ahmed, Md; Khan, Saleha; Arakawa, Osamu; Onoue, Yoshio (Biochimica et biophysica acta, 1995)
Unique substances of the hemagglutinating activity were separated from unialgal cultures of the toxic phytoflagellates, Chattonella marina and Gymnodinium sp. Molecular masses of the substances were estimated to be 14 000 in Chattonella and 15 000 in Gymnodinium. These two substances contained phosphorus, hexose (galactose) and glycerol in the following molar ratios; 1.00:1.18:1.24 ( Chattonella) and 1.00:1.07:1.10 ( Gymnodinium). Hemagglutinating titres using rabbit red blood cells were inferred to be 25 000 in both preparations. In the presence of Chattonella hemagglutinin (0.10-0.50 μM), the growth of C. marina in Provasoli's ES media was little affected during 24 h of incubation, whereas a marked suppression took place in growth of Gymnodinium sp. (50% inhibition, 0.12 μM) or the diatom Nitzschia closterium (0.17 μM). On the other hand, Gymnodinium hemagglutinin inhibited the growth of the three species of phytoplankton. A 50% inhibition occurred at 0.12 AM in C. marina, at 0.22 μM in N. closterium or at 0.50 μM in Gymnodinium sp.